Self-perceived employability in Spain. Issue 3 (12th March 2018) - Vargas, Reyes; Sánchez-Queija, María Inmaculada; Rothwell, Andrew; Parra, Águeda
Abstract : Purpose: The purpose of this paper is to validate the self-perceived employability (SPE) scale (Rothwell et al., 2008) and explore its relationship with sociodemographic variables in Spain. The SPE is an employability scale designed to examine undergraduates' expectations and self-perceptions of employability. The SPE includes internal and external dimensions of employability and has been satisfactorily tested in a variety of contexts. Design/methodology/approach: The sample comprised 1, 502 Spanish undergraduate students from a broad range of subject areas. Confirmatory factor analyses and exploratory factor analyses were conducted. Finally, the Spanish-self-perceived employability (S-SPE) was studied in relation to a set of demographic variables. Findings: The results revealed similar findings to those reported by Rothwell et al. (2008), namely, four factors labeled: the external labor market's demand for people in my subject field, my confidence in my skills and abilities, the status and credibility of my field of study and my engagement with my studies and academic performance. The external and internal employability dimensions were obtained by forcing a two-factor solution. Men scored higher than women in the S-SPE; science students scored higher than arts and humanities undergraduates and students with higher perceived income levels scored higher than those with lower perceived income levels. Originality/value: The S-SPE can be used with Spanish speaking university students (Spanish being the second most widely spoken language in the world) and allows cross-cultural comparisons of undergraduates' SPE. The S-SPE may help guide the development of social policies and programs designed to enhance employability. It can be used with undergraduates as a diagnostic instrument in career counseling, and as a self-assessment instrument which will enable undergraduates to acquire a greater degree of self-knowledge in relation to their employability.